KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI INPRES DOYO LAMA KABUPATEN JAYAPURA PROVINSI PAPUA - Dike, Yosina; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
Principal leadership is the ability to mobilize existing resources in a school whichwill be used optimally to achieve the expected goals. In this study, the main objectiveis to describe how a principal improves teacher performance in leadership. Techniques tocollect the data needed in this study use interview, observation, and documentationtechniques. For data using interactive analysis models from Miles and Huberman,namely collecting data, data reduction, data presentation, and drawing conclusions. Inthis research, it produces a leadership style carried out by the principal, such as using aleadership style that is seen in the processes that the principal goes through in meetingactivities, makes decisions, and acts in determining a solution or problem that arises. Inprincipal leadership, the principal is a reflection, motivator, and guide for teachers,students, and people involved in the school environment.